2020
DOI: 10.3168/jds.2019-17501
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Dietary bovine milk–derived exosomes improve bone health in an osteoporosis-induced mouse model

Abstract: Osteoporosis is a systemic skeletal disease characterized by low bone mass and micro-architectural deterioration of bone tissue, with a consequent increase in bone fragility and fracture susceptibility. In an aged society with increased life expectancy, the incidence rate of osteoporosis is also rapidly increasing. Inadequate nutrition may negatively influence bone metabolism. Recently, many studies have investigated the functionality of milk-derived exosomes, which play important roles in cell-to-cell communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 46 publications
3
53
0
1
Order By: Relevance
“…Increasing evidence has shown the therapeutic potential of exosomes in treating various bone diseases (30,31). The BMD of bovine colostrum exosome-fed glucocorticoid-induced osteoporosis mice was significantly improved compared with that of control mice without exosome treatment (32). In a femoral fracture model, mice treated with exosomes from human umbilical cord MSCs (HUCMSCs) cultured under hypoxic conditions showed a significantly larger callus volume and greater vascularity in the fracture site than those treated with exosomes from HUCMSCs cultured under normoxic conditions or with PBS (33).…”
Section: Discussionmentioning
confidence: 98%
“…Increasing evidence has shown the therapeutic potential of exosomes in treating various bone diseases (30,31). The BMD of bovine colostrum exosome-fed glucocorticoid-induced osteoporosis mice was significantly improved compared with that of control mice without exosome treatment (32). In a femoral fracture model, mice treated with exosomes from human umbilical cord MSCs (HUCMSCs) cultured under hypoxic conditions showed a significantly larger callus volume and greater vascularity in the fracture site than those treated with exosomes from HUCMSCs cultured under normoxic conditions or with PBS (33).…”
Section: Discussionmentioning
confidence: 98%
“…Increasing evidence has shown the therapeutic potential of exosomes in treating various bone diseases [30,31]. The bone mineral density of bovine colostrum exosome-fed glucocorticoid-induced osteoporosis mice was signi cantly improved compared with that of control mice without exosome treatment [32]. In a femoral fracture model, mice treated with exosomes from human umbilical cord MSCs (HUCMSCs) cultured under hypoxic conditions showed a signi cantly larger callus volume and greater vascularity in the fracture site than those treated with exosomes from HUCMSCs cultured under normoxic conditions or with PBS [33].…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, we found that miR-30a-5p, miR-22-3p, and miR-26a are highly conserved in colostrum and mature milk in cows, caprines, and humans, suggesting their possible importance in neonatal growth. Our results provide new insights and resources for discovering the noble functionality of immune-associated miRNAs from dietary exosome [37] and for developing infant formulas taking into account the differences on miRNA expression in human, bovine and caprine milk as well as evaluating biological features as diagnostic biomarkers.…”
Section: Comparative Analysis Of Mirnas From Human Bovine and Caprine Mature And Colostrum Milk-derived Exosomesmentioning
confidence: 95%